Seasonal integration and co-integration : modelling tourism demand in Singapore. - Chen, Yen Yu. (2013)
Japan has been an important market for the Singapore tourism sector. This study seeks to develop a tourism demand model for Singapore using Japanese quarterly data sets. Tests for unit roots at various seasonal frequencies as well as the zero frequency are carried out by using Hylleberg et al. (1993) test procedure. The results indicate that unit roots at zero frequencies are present in all series. Unit roots at biannual cycle are found to be present in tourist arrivals, income and relative price series whereas an annual cycle root is only present in the relative exchange rate series. Using the joint test for seasonal unit roots, we conclude that the series exhibit stationary seasonal patterns which allows us to model using deterministic seasonal dummies. A unique co-integrating relation is found to be present in the model.